Quality characteristics, fatty acid profiles, flavor compounds and eating quality of cull sow meat in comparison with commercial pork - Hoa, Van Ba (Asian-Australas J Anim Sci, 2020)
OBJECTIVE: Although the slaughter of cull sows (CS) for human consumption and meat products processing appears quite common throughout the world, relatively limited scientific information regarding the meat quality parameters of this pork type is available. The present study aimed at providing the technological quality characteristics and eating quality of CS meat, and comparing with those of commercial pork. METHODS: Longissimus thoracis et lumborum muscle samples of CS and finisher pigs (FP) at 24 h postmortem were collected and used for investigation of the meat quality traits (pH, color, shear force, cooking loss, water holding capacity), fatty acids, flavor compounds and sensory characteristics. RESULTS: The CS meat had significantly higher moisture content (p = 0.0312) and water holding capacity (p = 0.0213) together with lower cooking loss (p = 0.0366) compared to the FP meat. The CS meat also exhibited higher (p = 0.0409) contents of unsaturated fatty acids, especially polyunsaturated fatty acids (PUFA, p = 0.0213) and more desirable PUFA/total saturated fatty acids ratio (p = 0.0438) compared to the FP meat. A total of 56 flavor compounds were identified, amongst the amount of 16 compounds differed significantly between the two pork groups. Most of the PUFA-derived flavor compounds (e.g., hexanal, benzaldehyde, and hydrocarbons) showed higher amounts in the CS meat. While, 3-(methylthio)-propanal and 4-methylthiazole associated with pleasant aromas (meaty and roast odor notes) were only found in the FP meat. Furthermore, no differences were reported by panelists for flavor, juiciness, tenderness, and acceptability scores between the two pork groups studied. CONCLUSION: The sow meat exhibited better technological quality and its eating quality could be comparable to the commercial pork. This study provides meat processors and traders with valuably scientific information which may help to improve the utilization and consumption level of sow meat.